Penerapan Model Pembelajaran Reading Concept Connection Discussion Evaluation (RCCDE) Menggunakan Media Audio Visual Untuk Meningkatkan Hasil Belajar Siswa - Anatus Sholeha; Roudlotul Hikamah, Siti; Bokhori Muslim, Imam (Universitas Islam Jember, 2021)
Application of the Reading Concept Connection Discussion Evaluation (RCCDE) learning model to improve student learning outcomes on global warming material for the even semester of the 2019/2020 school year. The type of research used was classroom action assessment and the research subjects were grade VII students with 27 students consisting of 20 female students and 7 male students. Not all grade VII students have completed the KKM but 50% have completed the KKM. The results obtained showed that the student's average score reached 79.9% with a total classical completeness of 85.2%. So it can be concluded that the application of the RCCDE learning model can improve student learning outcomes. Keywords: Audio Visual Media, Learning Outcomes, RCCDE Model